2002
DOI: 10.1080/00343400120099898
|View full text |Cite
|
Sign up to set email alerts
|

New Media Industry Development: Regions, Networks and Hierarchies - Some Policy Implications

Abstract: Promotion of the new media industry has become a significant focus for regional development strategies, as it is generally believed that the new media industry is a highly desirable form of economic activity.But is this really so? The question was put to a group of international researchers. The article which summarizes their discussion and policy recommendations states that it is by no means clear that new media activities are preferable to other forms of economic activity in a region, which might be more sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…Additionally, despite the fact that the cluster phenomenon has recently caught the imagination and excitement of policy makers, cluster policies are hampered by a lack of empirical evidence, with many studies into the relationship between clusters and performance based on case studies (Swann, Prevezer, and Stout 1998;Backlund and Sandberg 2002;Cooke 2002Cooke , 2003Hallencreutz and Lundequist 2003). For those empirical studies available, investigations into performance were carried out at three levels as indicated in Table 1, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, despite the fact that the cluster phenomenon has recently caught the imagination and excitement of policy makers, cluster policies are hampered by a lack of empirical evidence, with many studies into the relationship between clusters and performance based on case studies (Swann, Prevezer, and Stout 1998;Backlund and Sandberg 2002;Cooke 2002Cooke , 2003Hallencreutz and Lundequist 2003). For those empirical studies available, investigations into performance were carried out at three levels as indicated in Table 1, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some insights from work on the new economy have been drawn upon to facilitate this analysis. Focusing on the working lives of people and the wider processes that shape development facilitates a critical analysis of urban and regional development and avoids the risk of capture by the boosterism of supportive agencies (Backlund and Sandberg 2002). In this case, gender divisions, the precarious position of and key role played by freelancers, and the possible contradictions between growth and learning have been highlighted.…”
Section: Resultsmentioning
confidence: 99%
“…The term new media refers to the "range of interactive digital products and services which offer new ways to trade, market, educate and entertain, delivered through the Internet, CD ROM, DVD, interactive TV and intranets" (Copeland 2000, 7; see also Backlund and Sandberg 2002;Batt, Christopherson, Rightor, and Van Jaarsveld 2001;Pratt 2000). Digitalization allows the fusion of different media formats (sound, graphics, video animation) and provides the technical foundations for unifying or defining the sector, which otherwise is quite diverse.…”
Section: The New Media Cluster In Brighton and Hovementioning
confidence: 99%
“…Such imbalances are worrying if only because they may well have serious implications for users and consumers of products and services, which have been designed by (predominantly) men, and thus arguably for men (Catherine Beavis 1998;Leslie Haddon 1999;Ann-Katrin Bäcklund and Å ke Sandberg 1999). However, addressing this situation is important not only for consumers, but for those working there too.…”
Section: Lisa Pittmentioning
confidence: 94%